Foreign exchange risk management by CTRM Aero Composites Sdn Bhd, Batu Berendam Melaka / Fiszatulhusna Nordin - Nordin, Fiszatulhusna (Faculty of Business and Management, 2010)
CTRM Aero Composites Sdn Bhd, Batu Berendam, Melaka (CTRM AC) was incorporated on 16th August 1994. CTRM Aero Composites is the 15th largest composites airframe supplier for Airbus UK. This company obtained their material sources such as glass fiber, carbon fiber, and AGS composites mainly from suppliers in Europe and US. Therefore, CTRM Aero Composites are using multi currencies transaction in their business and it’s important to realize the role that currencies play in the performance of company’ business. The aim of this paper is to study on how to Finance Department of CTRM Aero Composites Sdn Bhd (CTRM AC) manage the foreign currency exchange risk. This research has been conducted due to huge number of transaction done in relation to foreign currency exchange. Since CTRM AC transactions involve heavily in import (purchases) and export (sales), it is crucial for the company to measure and manage exchange rate risk exposure to reduce company’s vulnerabilities from major exchange rate movements, which could adversely affect profit margins and the value of assets. The methods use to complete the research are through primary sources of interviewing Finance Department staff as well as through secondary sources by reading of articles, journals and books related to the research. The result of the study shows the gap between the best practices on managing the foreign currency exchange risk with the current practice by Finance Department of CTRM AC. The result shows that there exist gap between procedures on managing foreign currency exchange risk current practice since the company do not have proper policy on managing the risk and not all hedging technique is fully utilized by the company. As a conclusion, there is no proper policy or procedures in managing foreign exchange risks by the company and CTRM AC use external forward contract extensively and try to apply hedging internally but ignoring other methods to hedge the foreign currency exchange risks.